2011
DOI: 10.1186/2047-783x-16-6-285
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T-Lymphopenia in HIV negative tuberculous patients at king khalid university hospital in riyadh, saudi arabia

Abstract: Tuberculosis (Tb) is a chronic infectious disease in which the cellular immunity (specifically CD4+ and CD8 lymphocytes) provides the most important defense in controlling infection. CD4 lymphopenia is a well-defined risk factor for the development of active tuberculosis in patients infected with Human Immunodeficiency Virus. In HIV - negative patients, CD4 and CD8 cell count suppression has been associated with Tb infection. Our study was designed to deter mine the baseline and post-treatment values of CD4 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 17 publications
8
38
3
Order By: Relevance
“…This finding was similarly observed by Pilheu JA et al and Al-Aska AI et al, who reported mean of 259.33±100.89/mm 3 and 1136.00±512.06 versus 1461.90±367.02 respectively. 11,12 In another study by Shijubo et al, they observed significantly decreased CD8+ T cell which is similar to our finding. 16 This finding could be related to the fact that protective immunity against TB requires CD8+ T cells which are seen to accumulate at the site of mycobacterial infection, forming a cuff at the periphery of epitheloid cell granulomas.…”
Section: Discussionsupporting
confidence: 91%
“…This finding was similarly observed by Pilheu JA et al and Al-Aska AI et al, who reported mean of 259.33±100.89/mm 3 and 1136.00±512.06 versus 1461.90±367.02 respectively. 11,12 In another study by Shijubo et al, they observed significantly decreased CD8+ T cell which is similar to our finding. 16 This finding could be related to the fact that protective immunity against TB requires CD8+ T cells which are seen to accumulate at the site of mycobacterial infection, forming a cuff at the periphery of epitheloid cell granulomas.…”
Section: Discussionsupporting
confidence: 91%
“…1A). T-lymphopenia was not observed in TB patients under our study, unlike reported in some studies [11].…”
Section: Resultscontrasting
confidence: 80%
“…19,46 For both Sjögren syndrome 47,48 and sarcoidosis, CD4 lymphopenia has been associated with more severe disease and/or consequences. 57,58 Infections can be associated with decreased cell counts, including diminished CD4 lymphocyte counts, and this should not be confused with ICL. 50,51 Similar to many primary immunodeficiencies, malignancies have been reported in ICL, suggesting that the incidence is higher than in the average population.…”
Section: Clinical Presentationmentioning
confidence: 99%